PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SAKTI PRIMA JAKABARING PALEMBANG - M. Devani Oktarian Oktarian; Arniza Nilawati; Lesi Agusria (DIBINOM : Digital Business, Economic Jurnal, 2025)
This study aims to determine the effect of work motivation and work environment on employee performance at PT. Sakti Prima in Jakabaring, Palembang. This research employed a quantitative approach with a survey method involving 61 respondents. Data were collected through questionnaires, and analyzed using multiple linear regression with t-tests, F-tests, and the coefficient of determination. The results indicate that work motivation has a positive and significant effect on employee performance. The work environment also has a positive and significant effect on employee performance. Simultaneously, work motivation and work environment contribute significantly to improving employee performance. These findings highlight the importance for companies to enhance motivation and create a conducive work environment to foster employee productivity.